The effects of the bank-internal ratings on the loan maturity - Nataliya Fedorenko; Dorothea Schäfer; Oleksandr Talavera (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The paper focuses on the effects of three different internal bank ratings - Risk-, Property- and Creditworthiness-Rating - on the loan maturity. We use a sample of about 5,000 loans given to sole proprietors and corporate borrowers by two German banks from January 2003 till July 2005. The estimation results for corporate borrowers are consistent with Diamond's (1991) predictions of non-monotonic relationship between ratings and maturity. The best rated and the worst rated loans tend to have shorter maturities than loans with an intermediate rating. However, our results for sole proprietors conflict with the predictions of Diamond and with the majority of the empirical literature. We find a negative association between ratings and maturity of the loans given to sole proprietors.
Keywords: C25; D82; G20; 330; loan maturity; internal bank ratings; risk of default; creditworthiness.; Kreditwürdigkeit; Kredit; Laufzeit; Deutschland